The implementation of the 1988 DECS minimum library standards for secondary schools in Ilocos Norte an assessment - Acleta, Minda Agustin 1945- (Diliman, Quezon City University of the Philippines, School of Library and Information Studies, 1996)
The purpose of the study is to assess the extent of compliance of the secondary school libraries in Ilocos Norte and Laoag City to the 1988 DECS Minimum Library Standards for Secondary Schools. Sixty-five public and private secondary schools in Ilocos Norte and Laoag City were surveyed for this study. Fifty-three of these are located in Ilocos Norte while twelve are in Laoag City. Three public schools in Ilocos Norte were not included in the study because these schools do not offer a complete secondary education at the time of the study. Out of the fifty secondary schools in Ilocos Norte, twenty-eight are public and twenty-two are private. In Laoag City, five are public and seven are private schools.
The normative descriptive survey method was used in this study. A survey questionnaire consisting of 6 parts and scheduled interviews were used in this study.
The findings revealed that not one public nor private secondary school among the sixty-two respondent schools was able to comply with most of the minimum requirements set forth in the DECS Bulletin No. 1, s. 1988. The non-awareness of the existence of the DECS Minimum Library Standards is the main reason cited by the majority of the respondents for non-compliance. Failure of the government to provide adequate funds has resulted in the recurrent budget deficit that is the cause of the inadequate collection of books, facilities, furniture and equipment in all the secondary schools. Very little effort is exerted in providing quality school library service in Ilocos Norte and Laoag City. This is a factor that can be attributed for the non-compliance with the DECS Standards. The lack of full-time school librarians is a contributing factor in the non-compliance of these libraries with the 1988 DECS Library Standards. Majority of the respondents recommended urgent measures such as a continuing library staff development program and the appointment of professional licensed librarians to make the libraries come up to the DECS Minimum Library Standards.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: School libraries -- Standards. -- Philippines -- Ilocos Norte; School libraries -- Evaluation. -- Philippines -- Ilocos Norte